2020
DOI: 10.1016/j.scitotenv.2020.136832
|View full text |Cite
|
Sign up to set email alerts
|

Removal of methylene blue from aqueous solutions by biochar prepared from the pyrolysis of mixed municipal discarded material

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
44
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 136 publications
(45 citation statements)
references
References 88 publications
0
44
0
1
Order By: Relevance
“…The sharp downfall in the removal efficiency after pH 7.0 could be owing to surface charge balancing as indicated by the PZC values. Hence, at a lower pH, the surfaces of the sorbents were dominated by positive charges, which tended to repel the positively charged MB dye ions resulting in lower removal efficiency 36 . However, as the pH of the solution increased from 3.0 to 7.0, the concentration of negative charges was increased on the surface of the sorbents, which in turn resulted in a higher removal efficiency at pH 7.0.…”
Section: Resultsmentioning
confidence: 99%
“…The sharp downfall in the removal efficiency after pH 7.0 could be owing to surface charge balancing as indicated by the PZC values. Hence, at a lower pH, the surfaces of the sorbents were dominated by positive charges, which tended to repel the positively charged MB dye ions resulting in lower removal efficiency 36 . However, as the pH of the solution increased from 3.0 to 7.0, the concentration of negative charges was increased on the surface of the sorbents, which in turn resulted in a higher removal efficiency at pH 7.0.…”
Section: Resultsmentioning
confidence: 99%
“…Tea waste (Uddin et al, 2009) 85.1 MMDM derived biochar (Hoslett et al, 2020) 7. 2Rice husk (Vadivelan and Vasanth Kumar, 2005) 40.59 PCM5 (This work) 109.9…”
Section: Comparison With Other Reported Adsorbentsmentioning
confidence: 99%
“…In this study, authors observed that the change of dosage of biochar increased the removal efficiency and increased the rate of adsorption, which agreed with the pseudo first order kinetic model theoretically. Similar to the method used by [111,115], which inferred using a pseudo second order kinetic model that, in the adsorption of methylene blue using biochar (municipal waste derived biochar), the rate limiting step was the chemisorption step, and that the pseudo second order kinetic model was much more efficient than the other models in describing the particulate and liquid film diffusion and surface adsorption processes.…”
Section: Adsorption Kinetic Studiesmentioning
confidence: 99%